ANALISIS PERSEPSI NASABAH PT. BANK SYARIAH INDONESIA PURWOKERTO TERHADAP KEBIJAKAN GREEN BANKING DALAM MENDUKUNG PROGRAM SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Ubaidillah, Ubaidillah; Sholikha, Akhris Fuadatis (Indonesian Scientific Journal of Islamic Finance, 2025)
Green banking represents a policy framework widely adopted by financial institutions to encourage environmentally sustainable practices. This study investigates the implementation of green banking policies at PT Bank Syariah Indonesia Tbk, particularly the Purwokerto Branch, and examines customer perceptions of these initiatives in relation to the Sustainable Development Goals (SDGs). Employing a qualitative field research approach, respondents included representatives from Bank Syariah Indonesia, the Financial Services Authority (OJK), the Ngudi Dadi Livestock Group, customers, and SMEs in Banyumas Regency. Data were analyzed using the Miles and Huberman model, with validity ensured through triangulation techniques. The results show that the bank has implemented green banking through defensive, preventive, offensive, and sustainable strategies, evaluated using the Green Coin Rating (GCR) framework covering indicators such as carbon emissions, green rewards, green building, reuse/recycle/refurbish, paperless systems, and green investment. Customer perceptions varied considerably, with most respondents demonstrating limited knowledge of green banking, although they expressed strong support for initiatives such as paperless transactions, green building design, energy and water efficiency, and mobile banking services. The study further highlights the importance of extending policy benefits beyond livestock farmers to other local SMEs, including traditional food producers, fish farmers, and waste bank communities, thereby fostering a more equitable distribution of benefits within society.